AB0286 A Cluster-Randomized Trial of a Behavioral Intervention to Incorporate a Treat-To-Target Approach in the Clinical Care of Rheumatoid Arthritis Patients. (9th June 2015) - Harrold, L.R.; Reed, G.W.; Harrington, J.T.; Barr, C.J.; Saunders, K.C.; Gibofsky, A.; Greenberg, J.D.; John, A.; Devenport, J.; Kremer, J.M.
Abstract : Background: A treat-to-target (T2T) approach to the care of patients with rheumatoid arthritis (RA) has been advocated, which involves regular assessment of disease activity using validated metrics, frequent follow-up visits for patients with moderate to high disease activity, and escalation of therapy when patients have inadequate therapeutic response as assessed by standard disease activity scores. Objectives: The goal of this abstract is to examine whether cluster randomization will result in comparable patients for a behavioral intervention trial designed to assess the impact of implementing a structured T2T approach vs routine care. Methods: This trial cluster-randomized 31 rheumatology practices based on practice size from the Corrona network of private and academic rheumatology sites to either the T2T intervention (n=16) or usual care (n=15) between July 29, 2011, and July 30, 2013. RA patients with moderate or high disease activity, defined as Clinical Disease Activity Index (CDAI) >10, and no contraindication to T2T were enrolled by the practices and followed for 12 months. In the T2T group, medications were to be accelerated based on disease activity levels with visits occurring as frequently as monthly in those with active disease. Treatment acceleration was defined as a new initiation or increase to the dose or frequency of a prescribed biologic or non-biologic DMARD, or changing route of methotrexate from oral to subcutaneous. In contrast, the usual care subjects were seen at least every 3 months with medication changes per the treating provider. The co-primary endpoints were achievement of low disease activity, defined as CDAI of ≤10, and an assessment of feasibility of implementing T2T in rheumatology practices (e.g., rates of treatment acceleration, frequency of visits, time to next visit conditional on disease activity, and probability of acceleration conditional on disease activity). Results: There were 249 patients enrolled from the T2T practices and 289 from usual care practices. The two groups were similar in terms of mean age, gender, and race but not for ethnicity (Table ). Patients were also similar in terms of education level, employment status, insurance type and clinical features (disease duration, rheumatoid factor seropositivity, tender joint count, swollen joint count, disease activity, and patient pain); however, functional status was different. Both groups had similar proportions of subjects receiving prednisone and methotrexate as well as similar dosing for those taking these medications. Study retention at 12 months (time window is 9 to 15 months after enrollment) was 83% of the usual care subjects and 79% of the T2T subjects. Conclusions: This cluster-randomized approach to implementing a behavioral intervention successfully identified similar patients for the two treatment arms for a study of T2T. Acknowledgements: The Corrona T2T study is sponsored by Corrona, LLC, with support from a development and subscription agreement/contract with Genentech and additional support from AbbVie. Disclosure of Interest: L. Harrold Employee of: University of Massachusetts Medical School, G. Reed Employee of: Corrona, LLC, J. T. Harrington Shareholder of: AbbVie, Amgen, BMS, GlaxoSmithKline, Johnson & Johnson, Pfizer and Roche, Consultant for: AbbVie, Amgen, Antares, AstraZeneca, Celgene, Horizon, Iroko, Pfizer, Roche and UCB, Speakers bureau: AbbVie, Amgen, Pfizer, Roche and UCB, C. Barr Employee of: Corrona, LLC, K. Saunders Employee of: Corrona, LLC, A. Gibofsky: None declared, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Novartis and Pfizer, Employee of: Corrona, LLC, A. John Employee of: Genentech, Inc, J. Devenport Employee of: Genentech, Inc, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: Genentech, Inc, Consultant for: Genentech, Inc, Employee of: Corrona, LLC